Penggunaan ModelPembelajaran Berbasis Proyek terhadap Penguasaan Mufradat Siswa Negeri 1 Sungai Penuh - Ulinnuha, Nur Atika Rima; Husein, Muhammad Fadhil (Institut Agama Islam Darul Fattah Lampung, 2024)
Thisdstudydaims to examineMthe effectivenessdof the ProjectMBased Learning (PjBL) modeldon the vocabularyd (mufradat) masterydof 10th-gradedstudents at MA Negerid1 Sungai Penuh. dVocabulary masterydis a crucial elementdin learning the Arabicdlanguage, asdvocabularydforms thedbasis of effectivedcommunication and deepdunderstanding of texts. Thisdresearch usesdan experimentaldmethod by comparing twodclasses: andexperimental classdusingdthe PjBL model and a control class usingdconventional methods. The results show that students in the experimental class demonstratedda significant improvementdin vocabularydmastery compared to students in the control class. Thedstudy concludes thatdthe applicationdof the PjBLdmodel isdeffective indenhancing studentsdArabic vocabulary mastery